2020
DOI: 10.18785/gcr.3101.09
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and Occurrence of Common Bottlenose Dolphins (Tursiops truncatus) in Three Estuaries of the Northwestern Gulf of Mexico

Abstract: IntroductIon Common bottlenose dolphins (Tursiops truncatus, Montagu, 1821) are globally distributed between the 60 th parallels in temperate to tropical oceanic and coastal waters, and estuarine populations have been documented throughout their range (Jefferson et al. 2008, Wells and Scott 2018). In the Gulf of Mexico (GOM), common bottlenose dolphins (hereafter referred to as "bottlenose dolphins") are widely distributed in bays, sounds, estuaries, and coastal waters, including the waters of Texas (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 36 publications
(58 reference statements)
3
14
0
Order By: Relevance
“…Travel between Texas bays has been documented in other studies for some individuals (Blaylock and Hoggard, 1994;Maze and Würsig, 1999;Lynn and Würsig, 2002;Ronje et al, 2020). Previous studies have identified changes in abundance aligning with annual temperature fluctuation in studies in Galveston and other Texas estuaries (Shane, 1980;Henningsen and Würsig, 1991;Fertl, 1994;Wilson et al, 1997;Ronje et al, 2020). As in UGB, dolphin abundance peaks during the summer in other northern Texas coastal locations and decreases with cooler temperatures (Fertl, 1994;Wilson et al, 1997;Ronje et al, 2020), while in central and south Texas the opposite pattern has been documented (Shane, 1980;McHugh, 1989).…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…Travel between Texas bays has been documented in other studies for some individuals (Blaylock and Hoggard, 1994;Maze and Würsig, 1999;Lynn and Würsig, 2002;Ronje et al, 2020). Previous studies have identified changes in abundance aligning with annual temperature fluctuation in studies in Galveston and other Texas estuaries (Shane, 1980;Henningsen and Würsig, 1991;Fertl, 1994;Wilson et al, 1997;Ronje et al, 2020). As in UGB, dolphin abundance peaks during the summer in other northern Texas coastal locations and decreases with cooler temperatures (Fertl, 1994;Wilson et al, 1997;Ronje et al, 2020), while in central and south Texas the opposite pattern has been documented (Shane, 1980;McHugh, 1989).…”
Section: Discussionsupporting
confidence: 53%
“…However, it is unknown if most remain in the lower Bay or if they leave the estuary to utilize nearby coastal waters, or travel to other estuaries. Travel between Texas bays has been documented in other studies for some individuals (Blaylock and Hoggard, 1994;Maze and Würsig, 1999;Lynn and Würsig, 2002;Ronje et al, 2020). Previous studies have identified changes in abundance aligning with annual temperature fluctuation in studies in Galveston and other Texas estuaries (Shane, 1980;Henningsen and Würsig, 1991;Fertl, 1994;Wilson et al, 1997;Ronje et al, 2020).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations